2022
DOI: 10.1155/2022/2005616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Hypothermia on the Results of Cardiopulmonary Resuscitation in a Cardiac Arrest Rat Model

Abstract: Objective. To investigate the optimal temperature of hypothermia treatment in rats with cardiac arrest caused by ventricular fibrillation (VF) after the return of spontaneous circulation (ROSC). Methods. A total of forty-eight male Sprague-Dawley rats were induced by VF through the guidewire with a maximum of 5 mA current and untreated for 8 min. Cardiopulmonary resuscitation (CPR) was performed for 8 min followed by defibrillation (DF). Resuscitated rats were then randomized into the normothermia (37°C) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Normothermia was defined as a body temperature of 37.5°C. The body temperature of animals treated with hypothermia was reduced to 34.0°C by using ice packs and electrical fan to achieve the target temperature quickly and maintained for the first 2 hours of post resuscitation (18,19). Afterward, the temperature was gradually increased to normothermia within 2 hours.…”
Section: Randomization and Post Resuscitation Carementioning
confidence: 99%
“…Normothermia was defined as a body temperature of 37.5°C. The body temperature of animals treated with hypothermia was reduced to 34.0°C by using ice packs and electrical fan to achieve the target temperature quickly and maintained for the first 2 hours of post resuscitation (18,19). Afterward, the temperature was gradually increased to normothermia within 2 hours.…”
Section: Randomization and Post Resuscitation Carementioning
confidence: 99%
“…Recent hypothermia drug studies have shown that these can eliminate shivering by acting on central or peripheral thermoregulatory pathways, and can also be used to treat conscious patients with hypothermia ( Lee et al, 2017a ). In animal experiments, cold temperature durations range from 30 min to 6 h, with 4 h commonly used ( Diao et al, 2020 ; Xu et al, 2022 ). Finally, rewarming rate is usually controlled at 0.5–2.0°C/h ( Diao et al, 2020 ; Xu et al, 2022 ) or as the fastest rewarming speed ( Jawad et al, 2021 ; Wang et al, 2022 ).…”
Section: Post-resuscitation Managementmentioning
confidence: 99%
“…In animal experiments, cold temperature durations range from 30 min to 6 h, with 4 h commonly used ( Diao et al, 2020 ; Xu et al, 2022 ). Finally, rewarming rate is usually controlled at 0.5–2.0°C/h ( Diao et al, 2020 ; Xu et al, 2022 ) or as the fastest rewarming speed ( Jawad et al, 2021 ; Wang et al, 2022 ).…”
Section: Post-resuscitation Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Одной из таких систем является тонко сбалансированная система гемостаза, которая ответственна за сохранение оптимального агрегатного состояния крови, предупреждение и остановку кровотечений, а также целостность кровеносных сосудов. реанимационных мероприятий [5] и используют животных в качестве моделей для изучения влияния гипотермии на гемостаз при сердечнолегочной реанимации. Авторы проведенного эксперимента доказали, что легкая гипотермия увеличивала сывороточные уровни физиологических антикоагулянтов у свиней [6].…”
unclassified